Castleman disease. Interaction with dermatopathy: Case report. (2020) - Modolin, M.L.A.; Camargo, C.P.; Milcheski, D.A.; Cintra, W.; Rocha, R.I.; Clivatti, G.M.; Nascimento, B.; Gemperli, R.
Highlights: We showed a different presentation of Castleman disease. Our service role out parasitic, mycotic, oncologic causes. Firstly we treat with antibiotics because the patient did not show any clinical improvement. We opted for a surgical treatment. All the decisions were discussed with the patient. The surgical treatment for soft tissue disease contributes to returning the patient's social and familial activities. Abstract: Introduction: Castleman disease (CD) is a lymphoproliferative disorder with lymph node hypertrophy. In the unicentric form (UCD), it affects one lymph node or chain of lymph nodes. In the multicentric form (DCM), there is hypertrophy of several lymph node chains with the formation of tumor masses, causing compressive symptoms. This case report showed a case of CD in a different location(inguinal region) associated to a multiple skin lesions. Presentation of the case: We reported a UCD in a 43-year-old female patient with no previous comorbidities. Since January 2016, this patient developed erysipelas lesions of the left leg (LL) from the thigh root to the foot. Concomitantly, a tumor mass appeared in the inguinal region. In 2019 we performed a biopsy that revealed changes characteristic of CD. Due to extremely poor trophic conditions, the skin area with erysipelas was resected, and the raw surface was grafted. Discussion: As an inference, the erysipelas may have been responsible for the subsequent lymphangitis, lymphedema and lymph node hypertrophy. Conclusion: Resection of the diseased skin and lymph node excision constitute the treatment of UCD and result in improvement of the clinical picture. Nevertheless, further study of the inflammatory reaction and of markers such as interleukin-6 and the presence of skin disorders in DC is needed.